2013
DOI: 10.1177/1359104513506427
|View full text |Cite
|
Sign up to set email alerts
|

‘Me and my Bump’: An interpretative phenomenological analysis of the experiences of pregnancy for vulnerable women

Abstract: Eight pregnant women, considered to be ‘vulnerable’ due to exposure to a number of underlying risk factors, participated in semi-structured interviews regarding their experiences of pregnancy and of Mellow Bumps, a 6-week targeted antenatal intervention. Interview transcripts were explored using interpretative phenomenological analysis. The analysis revealed five superordinate themes: pregnancy as a time of reflection; the body being taken over; pregnancy as an emotional rollercoaster; relationships as importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Our findings also correspond with those of others (Birtwell and others, ; Rolfe, ) in suggesting that, despite personal vulnerabilities and structural challenges, motherhood can be a positive experience for this group of women. Research has found that, for them, becoming a mother presented an opportunity ‘to set right the wrong of their past’ (Maxwell and others, ) in terms of their own family history and to stabilise their lifestyle and circumstances (Connolly and others, ).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also correspond with those of others (Birtwell and others, ; Rolfe, ) in suggesting that, despite personal vulnerabilities and structural challenges, motherhood can be a positive experience for this group of women. Research has found that, for them, becoming a mother presented an opportunity ‘to set right the wrong of their past’ (Maxwell and others, ) in terms of their own family history and to stabilise their lifestyle and circumstances (Connolly and others, ).…”
Section: Discussionsupporting
confidence: 91%
“…, Wan et al . , Birtwell & Hammond ) and small changes such as listening visits made a difference (characteristic 3) (Brugha et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…After extraction of papers, three studies were excluded as only presenting qualitative or case study data, 21,23,26,27 consistent with level V of AACPDM guidelines. All studies presented in Table I met levels III or IV of AACPDM levels of evidence.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Mellow Parenting was initially developed for use with children under age 5 years (Mellow Parenting), but has subsequently, without deviating from the core intervention format, been adapted for use with infants (Mellow Babies), antenatally (Mellow Bumps), and with fathers (Mellow Dads). Mellow Parenting and Mellow Babies have rapidly gained support with early years practitioners and have been recommended in UK national guidelines for evidence‐based parenting interventions and the California Evidence‐Based Clearinghouse for Child Welfare (http://www.cebc4cw.org/program/mellow-babies/); however, much of this evidence is derived from small case studies and qualitative studies . There is therefore a disjunction between positive representations of Mellow Parenting in practitioner reports and policy guidance compared with the relative lack of outcome‐driven, clinically informed research, such as adequately powered randomized trials.…”
mentioning
confidence: 99%